Respuesta :

Answer:

Logically that's not possible but if you want to prove it then, you have to use a trick.

Step-by-step explanation:

1 + 1 = 1 + [tex]\sqrt{1}[/tex]

        = 1 + [tex]\sqrt{(-1) * (-1)}[/tex]  

        = 1 + [tex]\sqrt{(-1)}[/tex] * [tex]\sqrt{(-1)}[/tex]

        = 1 + [tex]\sqrt{i^2}[/tex] * [tex]\sqrt{i^2}[/tex]

        = 1 + i * i  

        = 1 + i^2

        = 1 + (-1)

        = 1 - 1

        = 0

So, 1 + 1 = 0

Hope this will help. Please give me brainliest.

ACCESS MORE